Kaempferol is a novel antiviral agent against channel catfish virus infection through blocking viral attachment and penetration in vitro - Hao, Kai; Wang, Yu; Xu, Jie Hua; Nie, ChunLan; Song, SiYang; Yu, Fei; Zhao, Zhe (Frontiers in Veterinary Science, 2023)
Channel catfish virus (CCV, Ictalurid herpesvirus 1) is the causative pathogen of channel catfish virus disease, which has caused high mortality and substantial economic losses in the catfish aquaculture industry. Due to the lack of licensed prophylactic vaccines and therapeutic drugs, the prevention and control of CCV infection seems to remain stagnant. Active compounds from medicinal plants offer eligible sources of pharmaceuticals and lead drugs to fight against endemic and pandemic diseases and exhibit excellent effect against viral infection. In this study, we evaluated the antiviral ability of 12 natural compounds against CCV with cell models in vitro and found kaempferol exhibited the strongest inhibitory compound against CCV infection among all the tested compounds. Correspondingly, kaempferol decreased transcription levels of viral genes and the synthesis of viral proteins, as well as reduced proliferation and release of viral progeny, the severity of the CPE induced by CCV with dose-dependent manner, basing on quantitative real-time PCR (RT-qPCR), western blotting, viral cytopathic effects (CPE) and viral titer assessment. Moreover, time-of-drug-addition assays, virus attachment and penetration assays revealed that kaempferol exerted anti-CCV activity probably by blocking attachment and internalization of viral entry process.Altogether, the present results indicated that kaempferol may be a promising candidate antiviral agent against CCV infection, which shed light on the development of a novel and potent treatment for fish herpesvirus infection.